2019
DOI: 10.1088/1755-1315/399/1/012089
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of carbon steel in synthetic freshwater for water distribution systems

Abstract: Corrosion is one of the most common problems in water distribution systems. The purpose of this research is to investigate the corrosion rate of carbon steel in synthetic freshwater. The influence of a variety of time exposure that represents the actual conditions in practice was performed. Research conducted by weight loss methods using immersion test. The parameters of water quality were measured by using a multimeter portable (Hach HQ40d). From the experiments obtained that the corrosion rate of carbon stee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…However, over time, this oxide layer gradually decreases, and the corrosion rate begins to rise 33 . This observation parallels the findings of Royani et al, who observed a similar pattern in their investigation of the internal corrosion behavior of CS pipes within a freshwater environment 34 .
Figure 4 Effect of marine water salinity on CS pipe corrosion rate.
…”
Section: Resultssupporting
confidence: 91%
“…However, over time, this oxide layer gradually decreases, and the corrosion rate begins to rise 33 . This observation parallels the findings of Royani et al, who observed a similar pattern in their investigation of the internal corrosion behavior of CS pipes within a freshwater environment 34 .
Figure 4 Effect of marine water salinity on CS pipe corrosion rate.
…”
Section: Resultssupporting
confidence: 91%
“…The resulting matching obtained the oxides on the surface on carbon steel pipe are in the form FeO(OH) and Fe2O3.H2O. The result of corrosion products in the condensate environment are similar to studies of corrosion products in water environments [27][28][29][30]…”
Section: Figure 10supporting
confidence: 59%
“…Table 1. The chemical composition of low-carbon steel [11] Element (% wt). Fe C Cr Ni Mn Mo Al Si Cu S P Bal.…”
Section: Methodsmentioning
confidence: 99%